The Impact of Screen Time on Children’s Independence in Daycare Contexts: A Qualitative Study - Arih Haya Shofa (Qualitative Research in Early Childhood Education, 2026)
Background: The increasing presence of digital technology in young children’s daily lives has raised international concerns regarding its influence on developmental outcomes, particularly children’s independence. While excessive screen time is often associated with reduced autonomy, limited qualitative research has explored how children’s independence is shaped across different contexts, especially the interaction between daycare environments and home screen time practices in early childhood education. Purpose: This study aims to explore the impact of screen time on children’s independence in daycare settings and to understand how independence developed in daycare is maintained within the home environment. Methods: The study adopted a qualitative descriptive approach. Data were collected through semi-structured interviews with two children enrolled in a daycare center and two parents. The daycare context was selected as the primary educational setting, while parents provided perspectives on home practices. The interview data were analyzed using thematic analysis to identify recurring patterns and shared meanings related to independence and screen time. Findings: The findings indicate that daycare plays a significant role in fostering children’s independence through structured routines, consistent expectations, and opportunities for autonomous engagement. Screen time at home was reported to be controlled and non-addictive, with parents actively mediating digital device use. Such regulation allowed children’s independent behaviors developed in daycare to be sustained at home. Consistency between daycare practices and home routines emerged as a key factor in maintaining children’s independence across contexts. Conclusion: The study concludes that children’s independence is influenced more by environmental structure and adult mediation than by screen time exposure alone. These findings contribute to early childhood education by highlighting the importance of daycare–home consistency and providing practical implications for educators and parents in managing screen time to support children’s independence.